Ventral Hernioplasty in a Pulikulam Racing Bull – A Case Report - M. Madeena Begum; N. Krishnaveni; M. Revthi; M. Balagangatharathilagar; E. Madesh (The Indian Veterinary Journal, 2026)
A one-year-old Pulikulam bull was brought to the hospital with a history of gore injury and ventral abdominal swelling. On further enquiry, the owner reported that the ventral swelling was first noticed four months back immediately after the injury and it increased in size as the time progress. On physical examination reducible swelling was noticed in ventral abdomen. Under general anesthesia, the hernia ring was resected, herniorrhaphy and hernioplasty was done. Post operatively animal maintained with antibiotic and wound management. Animal had uneventful recovery.